Value Created by Culture in the Context of Sustainable Development: a Case Study of the Baltic States - Kiaušienė, Ilona; Mikalauskienė, Asta (Information & Media, 2020)
Culture is playing an increasingly important role in achieving sustainable development goals in countries. The value created by culture is important and an integral part of each country’s economy. The article is designed to establish the relationship between the value created by culture and the implementation of countries’ sustainable development goals through a detailed conceptualization of culture as an integral part of sustainable development. Conceptualization seeks to integrate culture into the concept of sustainable development by giving it three distinct roles in the process of evaluating sustainable development. The paper examines in detail the goals of sustainable development and their links with culture, highlighting the indicators that have been further used in the research. To assess the contribution of culture to the national economy, the number of cultural enterprises, value added in the cultural sector and turnover were estimated in order to compare employment in the cultural sector in different EU28 countries, and Min / Max indices were calculated. The study identified the relationship between the goals of sustainable development and the value created by culture, using a measure of connection strength. Statistical analysis of the data undoubtedly confirms that cultural contribution to the achievement of the SDGs is significant as there is a very strong positive relationship between the cultural value index and the SDGs achieved in all three case studies.
Keywords: sustainable development; sustainable development goals; culture; value created by culture